Influence of Different Soaking Methods On The Physical, Chemical And Functional Properties Of Starch Extracted From White Sorghum - M. Deepa, T. Poongodi Vijayakumar (International Journal of Advanced Science and Technology, 2020)
This present study is intended to examine the influence of five different soaking methods(aqueous alkali method (SIM01), aqueous alkali method with adjusted pH (SIM02), sodiummetabisulfite method (SIM03), lactic acid method (SIM04) and mercuric chloride method (SIM05))onthe physical, chemical and functional properties of starch extracted from white sorghum.The resultsindicated that, higheryield of starch with highest percentage of t6otal carbohydrate, high amylosecontent, maximum swelling power were observed in SIM01 method. However, flow properties andcompressibilityof starch extracted by SIM02 method was higher thanother methods.The hydrationcapacity and index of the starch extracted by SIM04 method was significantly high, which could bedue to smaller particle size.